Numerical Analysis of Autonomous Tractors on S-shaped Track based on math models - Sahatun; Mohamad Yamin (Master Program in Mechanical Engineering, Gunadarma University, 2023)
Autonomous vehicles today have increased the attention of academics, the industrial sector, and agriculture with intelligent vehicle technology that showcases multidisciplinary science using a range of Artificial Intelligence (AI) equipped with sensors and controls. One of the things that are needed in agriculture is an autonomous tractor to relieve all the work in the agricultural field. Therefore, this study aims to analyze the speed of an autonomous tractor path with S coordinates with a speed of 18 km/h and a time of 15 sec to determine how strong the vehicle performs when driving on a winding lane and improve driver safety. In this study, a numeric analysis of the speed of the autonomous tractor path was carried out using a simulation method using Carsim software based on the Math Model. The numerical results obtained in graphs and curves demonstrate the simulator can analyze tractor performance, reduce accident rates, and improve safety in agriculture.